2019
DOI: 10.1108/pm-03-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Older people and home ownership: the intention to relocate

Abstract: Purpose The purpose of this paper is to explore older people’s intention to relocate from their primary homes. The study also seeks to understand the policy implications that such intentions may have. Design/methodology/approach This study employs a survey-based design via computer-aided telephone interviews (CATI). The CATI survey was employed to gather information on the behaviour of older people and whether differences exist by gender, age, health immigration status and financial knowledge. The survey-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The need to improve digital literacy and thereby digital banking skills in older Australians is well‐recognised. 29 , 30 A limitation is that programs tend to be localised and small. There is a need to evaluate programs, identify best practices and develop programs with national reach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to improve digital literacy and thereby digital banking skills in older Australians is well‐recognised. 29 , 30 A limitation is that programs tend to be localised and small. There is a need to evaluate programs, identify best practices and develop programs with national reach.…”
Section: Discussionmentioning
confidence: 99%
“…Older people are known to turn to family, older friends and trusted others to manage their digital banking. 29 This can leave all parties at risk, and, at present, safeguarding policies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found significant numbers of people have already downsized, intend to, or would consider it (Duncan, James et al 2016;James, Rowley et al 2020). Other research suggests that Australians over 65 tend to live in larger dwellings than younger cohorts (despite having smaller household sizes), generally do not wish to move, and when they do move it is often to upsize (James, Rowley et al 2019;Judd, Liu et al 2014;Lowies, Whait et al 2020).…”
Section: Supporting Innovation In Alternative Housing Modelsmentioning
confidence: 99%
“…Such differences are often associated with changing housing aspirations over time and life-course events (Beer et al. , 2011b; Crawford and McKee, 2018; Lowies et al. , 2019; Preece et al.…”
Section: Literature Review: Intergenerational and Generational Housin...mentioning
confidence: 99%
“…Likewise, Hoolachan and McKee (2019, p. 213) draw upon Mannheim to set a contextual basis arguing that Mannheim's theory "was attentive to heterogeneities within a generation, as well as inter-generational differences". Such differences are often associated with changing housing aspirations over time and lifecourse events (Beer et al, 2011b;Crawford and McKee, 2018;Lowies et al, 2019;Preece et al, 2020) and the potential for inter-generational resource transfer (Lux et al, 2018). As an example of this K€ oppe (2018) observes how those young adults who live with parents for longer are more able to purchase a home more quickly than those renting, while an earlier study of life chances in the housing market by Payne and Payne (1977) found that housing status pathways are reinforced by social conditions and socially structured inequalities.…”
Section: Inequalities Of Housing Tenure and Housing Typementioning
confidence: 99%